Agrotechnology of Cultivating the Culture as a Repeat Cropping - Ergashboevna, Kholdarova Dilpuza (American Journal of Biodiversity, 2025)
The article presents information on agricultural technologies for growing mallow as a repeat crop on lands vacated by winter wheat.